Technology will save the climate! Attitudes towards Norway's climate policy in four social groups - Åsta Dyrnes Nordø; Gisle Andersen; Christine Merk (Kiel Institute for the World Economy (IfW Kiel), 2023)
The risk of opposition from the population increasingly plays a role in choosing the climate policy measures to achieve the objective to substantially reduce greenhouse gas emissions. In Norway, there is a long-standing cross-party consensus that the development of new technologies will be crucial for solving climate challenges. Comparing public opinion surveys, Norwegians are significantly more convinced that new technology will solve problems induced by climate change, compared people in other European countries. A concrete example of such a technology is carbon capture and storage (CCS). Despite discussions about the costs of establishing the technology, there is a cross-party consensus in Norway that CCS is a good and suitable measure for reaching climate policy goals. In this article, we review the historical background that has led to this broad support in Nor-way. Furthermore, we look at how this has been expressed in the political parties' attitudes towards CCS. There has been a long standing consensus among all major parties that CCS should be developed and deployed. We argue that this lay the foundation for the societal support for CCS. We analyze data from the Norwegian Coordinated Online panels for research on DEMocracy and governance (KODEM) to examine the attitudes toward CCS among citizens and three functional elites, namely elected representatives, bureaucrats, and journalists. We find that CCS receives strong support in all four groups, but that citizens and elected representative are more skeptical compared to bureaucrats and journalists. However, when looking at the factors that influence the perception of CCS, the pattern is the same for all four groups. The more technology optimistic a person is, the more positively they tend to perceive CCS as a method to fight climate change. We also find that those who think the political efforts to reduce greenhouse gases are too great are less positive about CCS com-pared to those who think the efforts are appropriate or too small. Overall, the analysis indicates that all four societal groups are technology optimistic and characterized by the same attitudes toward climate change. We discuss the role of technology optimism in Norway's climate policy and the reasons for the high degree of political consensus across groups with different societal functions.
Keywords: Q54; Q55; Q58; 330; Climate policy; carbon capture; CCS; technology optimism; citizen-elite congruence